Stanniocalcin 1 and ovarian tumorigenesis - Liu, Guangzhi; Yang, Gong; Chang, Bin; Mercado-Uribe, Imelda; Huang, Miao; Zheng, Jingfang; Bast, Robert C; Lin, Sue-Hwa; Liu, Jinsong (JNCI : Journal of the National Cancer Institute, 2010)
Stanniocalcin 1 (STC1) is a secreted glycoprotein hormone. High expression of STC1 has been associated with several cancers including ovarian cancer, but its role in the development of ovarian cancer is not clear. We used five human ovarian epithelial cancer cell lines (OVCA420, OVCA432, OVCA433, SKOV3, and HEY), immortalized human ovarian surface epithelial cells (T29 and T80), ovarian cancer tissues from 342 patients, serum from 73 ovarian cancer patients and from58 control subjects, and 116 mice, with six or eight per group. Protein expression was assessed. Cells overexpressing STC1 protein were generated by ectopic expression of human STC1 cDNA. STC1 expression was silenced by using small interfering RNA against STC1. Cell proliferation, migration, colony formation, and apoptosis were assessed. Xenograft tumor growth in mice was studied. Neutralizing anti-STC1 antibody was used to inhibit STC1 function. All statistical tests were two-sided. STC1 protein expression was higher in all human ovarian cancer cell lines examined than in immortalized human ovarian epithelial cell lines, higher in ovarian cancer tissue than in normal ovarian tissue (P < .001), and higher in serum from ovarian cancer patients than from control subjects (P = .021). Ovarian cancer cells with STC1 overexpression, compared with corresponding control cells, had increased cell proliferation, migration, and colony formation in cell culture and increased growth of xenograft tumors in mice. These activities in normal or malignant ovarian cells with STC1 overexpression, compared with control cells, were also accompanied by increased expression of cell cycle regulatory proteins and antiapoptotic proteins but decreased cleavage of several caspases. Within 24 hours of treatment, apoptosis in cultures of HEY ovarian cancer cells treated with neutralizing anti-STC1 monoclonal antibody was higher (17.3% apoptotic cells) than that in cultures treated with mouse IgG control cells (4.4%) (12.9% difference, 95% confidence interval = 11.6% to 14.2%). STC1 protein may be involved in ovarian tumorigenesis.